Corrigendum and Errata to Samuel C. Rickless's "Locke on the Probability of the Mind's Immateriality," Locke Studies 20 (2020): 1-28, https://doi.org/10.5206/ls.2020.10677 - Rickless, Samuel C. (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2021)
This article contains corrections to Rickless’s article “Locke on the Probability of the Mind’s Immateriality” published in Locke Studies 20 (2020). The original article may be found at the article’ homepage. Rickless provides a corrigendum to his interpretation of Nicholas Jolley’s Locke’s Touchy Subjects. The editor notes three errata, which have been corrected in the original article.